A general benzylic C–H activation and C–C coupling reaction of zirconocenes mediated by C–N bond cleavage in tert-butylisocyanide – unusual formation of iminoacyl complexes. Issue 44 (17th October 2019) - Arndt, Perdita; Reiß, Melanie; Spannenberg, Anke; Schünemann, Claas; Reiß, Fabian; Beweries, Torsten
Abstract : Reactions of the zirconocene alkyne complex [ rac -(ebthi)Zr(η 2 -Me3 SiC2 SiMe3 )] ( rac -(ebthi) = rac -1, 2-ethylene-1, 1′-bis(η 5 -tetrahydroindenyl)) with tert -butylisocyanide and methylbenzenes were investigated. Abstract : Reactions of the zirconocene alkyne complex [ rac -(ebthi)Zr(η 2 -Me3 SiC2 SiMe3 )] ( rac -(ebthi) = rac -1, 2-ethylene-1, 1′-bis(η 5 -tetrahydroindenyl)) with tert -butylisocyanide and methylbenzenes were investigated. Depending on the stoichiometry, the solvent and the reaction temperature different products were obtained. Starting with the end-on coordination of the isocyanide to the zirconium centre (2 ), elevated reaction temperatures and an excess of tert -butylisocyanide resulted after the elimination of the alkyne in the formation of zirconocene η 2 -iminoacyl cyanide complexes 3a–d . These complexes are formed by coupling with a benzyl fragment through C–H bond activation of a methyl group of methylbenzene. The dimeric cyanide bridged zirconocene complex 4 is formed as a side-product of this process. The unexpected dimer and the heterometallacycles were fully characterised, including X-ray crystallography.